2019
DOI: 10.1007/s00268-019-05251-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin is an Independent Predictor for Hungry Bone Syndrome After Parathyroidectomy

Abstract: Background Hungry bone syndrome is characterized by prolonged and severe hypocalcemia following parathyroidectomy. Previously, we reported that preoperative alkaline phosphatase is a major factor predicting prolonged hospital stay. Nonetheless, some patients with low alkaline phosphatase levels presented with hungry bone syndrome, suggesting that additional factors may play a role. Methods From September 2010 to December 2017, consecutive dialysis patients who underwent parathyroidectomy for secondary hyperpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In a prospective randomized study with 102 patients, there was no statistically significant benefit of using vitamin D (cholecalciferol) in patients with vitamin D deficiency to reduce HBS incidence after parathyroidectomy; this study demonstrated a raised incidence of HBS in younger individuals [16]. It has been postulated that AP is the best HBS predictor after parathyroidectomy [17]. In this case, values of AP oscillated between 600 and 2000 UI/L before surgery.…”
Section: Discussionmentioning
confidence: 66%
“…In a prospective randomized study with 102 patients, there was no statistically significant benefit of using vitamin D (cholecalciferol) in patients with vitamin D deficiency to reduce HBS incidence after parathyroidectomy; this study demonstrated a raised incidence of HBS in younger individuals [16]. It has been postulated that AP is the best HBS predictor after parathyroidectomy [17]. In this case, values of AP oscillated between 600 and 2000 UI/L before surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Secondly, the sample size in this study was relatively small, and the potentially significant association between variables might be covered. Thirdly, this study did not monitor the potential risk factor indexes of HBS mentioned in other studies, including 1,25 (OH) 2 D level, bone-ALP level, osteocalcin, and weight of the resected parathyroid gland, which might have certain influence on the results [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…A study on 260 participants with RHPT referred for PTx confirmed that elevated AP, but also osteocalcin, as well as subtotal PTx and a younger age were correlated with a longer hospital stay amid HBS (according to different types of regression analyses with statistically significant results). On point, serum osteocalcin raised from a median of 264 ng/mL at baseline to 468 ng/mL following PTx (p < 0.001) [112]. One study showed that HBS-related bone pain positively correlated with pre-operatory PTH and post-surgery osteocalcin and negatively associated with post-PTX values of bone AP and Klotho [113].…”
Section: Discussionmentioning
confidence: 99%
“…An amount of 23 studies were retrospective and 4 were of prospective, prospective-retrospective type, respectively, longitudinal and a national database cohort. Considering the number of enrolled participants per study, 12 studies included less than 100 participants per study, as follows: 19 (n = 2), 35, 37 (n = 2), 41, 45, 53, 62, 77, 79, 84; 9 studies enrolled between 100 and 200 individuals per study (of 108, 115, 120, 130, 131, 141, 148, 167, and 196), 3 studies had between 200 and 300 patients per study (specifically, 252, 260, and 297) while 3 larger studies had more than 700 patients per study (N = 796, 1846, and 7171), regardless the study design, a total of 12,468 patients with RHPT [1,4,17,30,40,84,85,[104][105][106][107][108][109][110]112,116,117,[123][124][125][126][127][128][129][130][131][132] (Table 5).…”
Section: Post-operatory Findings In Rhpt: Focus On Hbsmentioning
confidence: 99%